Greenhouse Gas Emission in Italian Mediterranean Buffalo According to Two Different Feed Sources: Preliminary Study - Sarubbi, Fiorella; Pappalardo, Raffaele; Grazioli, Giuseppe; Auriemma, Giuseppe (European Journal of Applied Sciences, 2023)
Greenhouse gas emissions (GHG) in animal husbandry depend on several factors. Among the greenhouse gases, the methane (CH4) deriving from enteric fermentation and ammonia emissions is the ones that encounter the greatest attention in ruminant breeding. The study was conducted in the two farms located in southern Italy. To determine the enteric greenhouse gas emissions from buffalo, information about animal production and farm management was analysed and using the Global Livestock Environmental Assessment interactive mode (GLEAM-i). In this experiment, the buffalo were fed with two types of unifeed ad was calculated CO2, CH4 and N2O emission produced. The resulting values of GHG emission from each production system were analysed using the t - test procedure using SPSS® version 26. The dry forage diet system had the highest GHG emission compared to green forage diet system, indicating the effect of higher inputs in the dry system in increasing GHG emission. From the results, greener management using feed and other management inputs would not only improve productivity, but also reduce the contribution of livestock to global greenhouse gas emissions.